Anfibolitos itaguara com assinatura e-morb: prováveis integrantes de ofiolitos paleoproterozoicos do sul do Cráton do São Francisco - Arianne de Souza Barbosa (2021)
Ophiolites are lithotypes from the oceanic crust that are positioned on continents through collisional processes. An ophiolitic sequence is characterized from top to bottom by pelagic metasediments, metabasic rocks, metagabbros and metaultramafic rocks. In the south of the São Francisco craton, between the cities of Itaguara and Crucilândia (Minas Gerais-Brazil), the Itaguara Sequence is located, composed of quartzites, schists, banded iron formations, ortho-amphibolites and metaultramafic rocks of paleoproterozoic age. The present work presents petrographic and lithochemistry data of amphibolites from the Itaguara Sequence. The Itaguara amphibolites have gabbro as protolith and are constituted by ortho- and clinopyroxene, plagioclase, hornblende and quartz. The lithogeochemical data reveal a tholeiitic affinity and an E-MORB signature, positioning them as coming from oceanic crust. It is suggested here that the Itaguara amphibolites would be associated with the base of a paleoproterozoic ophiolitic sequence. This sequence is associated with a possible ocean basin that was subducted in the Rhyacian-Orosirian orogenetic event between the Divinopólis and Campo Belo/Bonfim Metamorphic Complexes, where remnants of khondalite, accretionary prism and retroeclogite occur.